Penile Fracture: Simultaneous Complete Urethral Rupture with Bilateral Corpora Cavernosa Rupture - Ibrahim Alnadhari; Osama Abdelhaleem Abdeljaleel; Venkata Ramana Pai Sampige; Ausama Abdulmuhsin; Ahmad Shamsodini (Case Reports in Urology)
Penile fracture is not uncommon blunt trauma to the penis. Here, we present a rare case of penile fracture during sexual intercourse. The patient presented with penile swelling, bleeding per urethra, and inability to pass urine. Retrograde urethrogram showed significant extravasation of contrast from anterior penile urethra and no contrast passing to proximal urethra. Surgical exploration showed complete urethral rupture and bilateral cavernosal rupture. This case represents the value of urethrogram to evaluate the urethral injury and the association of complete urethral injury with bilateral ventral cavernosal injury.